Obesity Indices for Predicting Functional Fitness in Children and Adolescents With Obesity - Udomittipong, Kanokporn; Thabungkan, Teerapat; Nimmannit, Akarin; Tovichien, Prakarn; Charoensitisup, Pawinee; Mahoran, Khunphon (Frontiers in Pediatrics, 2021)
Objectives: We aimed to determine the obesity indices that affect six-minute walk test (6-MWT) distance in children and adolescents with obesity, and to compare the 6-MWT distance of obese subjects with that of normal weight subjects. Methods: Obese children and adolescents aged 8-15 years and normal weight age- and gender-matched controls were enrolled. All participants performed the 6-MWT; respiratory muscle strength (RMS), including maximal inspiratory pressure and maximal expiratory pressure; and spirometry. Data between groups were compared. In the obesity group, correlation between obesity indices and pulmonary function testing (6-MWT, RMS, and spirometry) was analyzed. Results: The study included 37 obese and 31 normal weight participants. The following parameters were all significantly lower in the obesity group than in the normal weight group: 6-MWT distance (472.1±66.2 vs. 513.7±72.9 m; p=0.02), forced expiratory volume in one second/forced vital capacity (FEV1/FVC) (85.3±6.7% vs. 90.8±4.5%; p<0.001), forced expiratory flow rate within 25-75% of vital capacity (FEF25%-75%) (89.8±23.1 vs. 100.4±17.3 %predicted; p=0.04), and peak expiratory flow (PEF) (81.2±15 vs. 92.5±19.6 %predicted; p=0.01). The obesity indices that significantly correlated with 6-MWT distance in obese children and adolescents were waist circumference-height ratio (WC/Ht) (r=-0.51; p=0.001), waist circumference (r=-0.39; p=0.002), body mass index (BMI) (r=-0.36; p=0.03), and chest circumference (r=-0.35; p=0.04). WC/Ht was the only independent predictor of 6-MWD by multiple linear regression. Conclusions: Children and adolescents with obesity had a significant shorter 6-MWT distance than normal weight subjects. WC/Ht was the only independent predictor of 6-MWT distance in the obesity group.